Alternativas metodológicas para revisão de matemática para alunos do 6º ano - MEIRELES, Francisco Xavier Campelo (2022)
his article has as its theme, methodological alternatives for reviewing mathematics for students of the 6th year of elementary school, aims to review the basic operations of mathematics using methodologies already studied that can be easily applied in the classroom. It stands out in this research a study on teaching and learning, the role of the teacher and the methodologies that help in learning the basic operations, which are: Table of Pythagoras; Multiplication by hand; Chinese multiplication, the division by sum process and complementary activities for teaching and learning basic operations.